Proposed Prototype for Multimedia Protocol in m-Health to Support a Communication between Patient and Hospital - Naktal Moaid Edan (Tikrit Journal of Pure Science)
Rapid advances in wireless communications and networking technologies, linked with advances in computing and medical technologies, facilitate the development and offering of emerging mobile systems and services in the healthcare sector. The objective of this paper is to identify the overview of the current multimedia communication protocols used in m-Health, such as SIP, RTCP, RTSP and RTP; and the challenges of mobile health systems, devices, and services. Also, propose a scenario to support communication between the patient and the hospital. m-Health systems will significantly affect the delivery of patient’s data in an ambulance; however, their exploitation in daily practice remains to be achieved.